Literasi Keuangan Bagi Siswa /I Di SMP Negeri 1 Arso Kota - Cornelia Desiana Matani; Hastutie Noor Andriati (UNIVERSITAS CENDERAWASIH, 2021)
This service activity aims to improve the financial literacy of junior high school students at SMP Negeri 1 Arso City, Keerom Regency. The training will be held on September 24, 2021, in the class room of SMP Negeri 01 Arso Kota, Keerom Regency. The participants of the activity were 40 students aged 13-16 years. The training was carried out by introducing the basic concepts of finance, the importance of managing finances, how to manage finances at a young age, and a basic understanding of taxes. Financial literacy needs to be taught as early as possible so as to increase our awareness of the importance of the ability to manage personal finances which in turn brings discipline in managing finances at a higher level. The monitoring and evaluation mechanism of training activities is carried out through the distribution of forms that assess students' understanding after the material is given which is distributed to training students after the activity.